Review of Research Works Done in Finance (4) - محمد صادقی (تحقیقات مالی, 1995)
In this section of the Journal, a summary of theses Completed at the M.B.A Level is presented. The title of these are: 1- The effect of financing methods on the stock price on the Tehran stock Exchange by MOHAMMAD RAHMANI 2- The effect of money supply on the Exchange rate in Iran By MINUO KIANI -RED 3- An Investigation of the reasons for price volatility of stock price an Tehran on the Stock Exchange By MEHDI ZARANDI .